SIMULATION OF MULTI-DISCHARGE COMPUTERS Of FUNDS - Gamayun , V. P. (Problems of Informatization and Control, 2021)
Methods, an arithmetic-algorithmic basis for constructing models for the study of multi-bit computer tools are proposed. An alternative approach is to use data structures and corresponding methods, processing algorithms based on bit-logarithmic coding of information.